Probing Experience From Assessment of User Emotions and Behaviour to Development of Products - Westerink, Joyce; Ouwerkerk, Martin; Overbeek, Therese J. M.; Pasveer, W. Frank; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
This book adheres to the vision that in the future compelling user experiences will be key differentiating benefits of products and services. Evaluating the user experience plays a central role, not only during the design process, but also during regular usage: for instance a video recorder that recommends TV programs that fit your current mood, a product that measures your current level of relaxation and produces advice on how to balance your life, or a module that alerts a factory operator when he is getting drowsy. Such systems are required to assess and interpret user experiences (almost) in real-time, and that is exactly what this book is about. How to achieve this? What are potential applications of psychophysiological measurements? Are real-time assessments based on monitoring of user behavior possible? If so, which elements are critical? Are behavioral aspects important? Which technology can be used? How important are intra-individual differences? What can we learn from products already on the market? The book gathers a group of invited authors from different backgrounds, such as technology, academy and business. This is a mosaic of their work, and that of Philips Research, in the assessment of user experience, covering the full range from academic research to commercial propositions.
Probing in Order to Quantify -- Experience in Products -- Inquiring about People’S Affective Product Judgements -- Atmosphere Metrics -- In Search of The X-Factor to Develop Experience Measurement Tools -- Probing Experiences: Logs, Traces, Self-Report and A Sense of Wonder -- Objective Emotional Assessment of Industrial Products -- Measuring Experiences in Gaming and TV Applications -- Sensing Affective Experience -- Brain, Skin and Cosmetics: Sensory Aspects Objectivated by Functional Magnetic Resonance Imaging -- The Assessment of Stress -- Discovery of T-Templates and Their Real-Time Interpretation Using Theme -- Probing in Order to Feed Back -- Where Will The User “Drive” Future Technology? -- A Wearable Emg Monitoring System for Emotions Assessment -- Computing Emotion Awareness Through Galvanic Skin Response and Facial Electromyography -- Unobtrusive Sensing of Psychophysiological Parameters -- It’S Heart Rhythm Not Rate That Counts -- TRansformative Experience on The Home Computer -- The Emotional Computer Adaptive to Human Emotion -- Using Physiological Measures For Task Adaptation -- The Usability of Cardiovascular and Electrodermal Measures for Adaptive Automation.
Keywords: User interfaces (Computer systems).; Input-output equipment (Computers).; Artificial intelligence; Computers; User Interfaces and Human Computer Interaction; Input/Output and Data Communications; Artificial Intelligence; Theory of Computation